2022
DOI: 10.15585/mmwr.su7103a5
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions to School and Home Life Among High School Students During the COVID-19 Pandemic — Adolescent Behaviors and Experiences Survey, United States, January–June 2021

Abstract: Youths have experienced disruptions to school and home life since the COVID-19 pandemic began in March 2020. During January–June 2021, CDC conducted the Adolescent Behaviors and Experiences Survey (ABES), an online survey of a probability-based, nationally representative sample of U.S. public- and private-school students in grades 9–12 (N = 7,705). ABES data were used to estimate the prevalence of disruptions and adverse experiences during the pandemic, including parental and personal job loss, homelessness, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 10 publications
0
50
0
Order By: Relevance
“…In one systematic review, it was estimated that child depression nearly doubled from 13% to 25% and anxiety from 12% to 21% [ 8 ]. Other studies have found obesity rates in children and adolescents increased from 19% to 22% within the first year of the pandemic, while physical activity and nutrition decreased [ 5 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one systematic review, it was estimated that child depression nearly doubled from 13% to 25% and anxiety from 12% to 21% [ 8 ]. Other studies have found obesity rates in children and adolescents increased from 19% to 22% within the first year of the pandemic, while physical activity and nutrition decreased [ 5 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, these disruptions to child and adolescent activities and changes in PH and MH have been inequitably distributed across race/ethnicity [ 6 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. School closures and provision of online or in-person schooling varied by race/ethnicity, as did access to various school activities [ 12 , 13 , 20 ]. Prevalence of MH disorders (e.g., anxiety and depression) have also been found to be much higher among Black and Hispanic children and adolescents [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary care clinicians will be busy for the foreseeable future, continuing to manage COVID testing, vaccination, and disease; managing other childhood illnesses; and helping families address COVID-related issues like delayed lead screening, routine immunization, and the negative mental health burden most visible in teenagers. 5 , 6 , 7 , 8 Burkhardt et al have created a document that will support primary care clinicians as they strive to provide high quality health care to children and address the inevitable future challenges of the COVID-19 pandemic and its sequelae.…”
mentioning
confidence: 99%
“…Additional aspects of ABES help us reach a broader understanding of child mental health, not just the impact of family hardship and school connectedness but also the negative impact of perceived racism on mental health (Mpofu et al, 2022). The data also point to the complexity of factors that negatively impact mental health such as the intersectionality of social determinants of health and adverse experiences particularly among gay, lesbian, or bisexual students (Krause et al, 2022). Thus, by the questions it asked, the ABES offers an explication of the specific ways family, community, and environment impact mental health.…”
mentioning
confidence: 99%